2007
DOI: 10.1021/jm070032y
|View full text |Cite
|
Sign up to set email alerts
|

9-(2-C-Cyano-2-deoxy-β-d-arabino- pentofuranosyl)guanine, a Potential Antitumor Agent against B-Lymphoma Infected with Kaposi's Sarcoma-Associated Herpesvirus

Abstract: Several 9-(2-C-cyano-2-deoxy-l-beta-d-arabino-pentofuranosyl)purine derivatives were tested against Kaposi's sarcoma-associated herpesvirus (KSHV)-infected primary effusion lymphoma (PEL) cells. The guanine derivative (3, CNDAG), as well as the 2-amino-6-substituted-purine derivatives 4, 5, and 6, exhibited cell growth inhibitory activity against KSHV-infected cells, but showed no cytotoxicity against KSHV-negative cells at >15 microM concentrations. Therefore, it was found that compounds 3, 4, 5, and 6 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our original plan was to install an acetonitrile group on the aromatic ring through transition‐metal‐catalyzed C(sp 2 )–H activation assisted by 8‐aminoquinoline because the nitrile group plays an important role in bioactive molecules and pharmaceuticals . However, preliminary experimental results showed that a methylation product was actually obtained when 2‐methyl‐ N ‐(quinolin‐8‐yl)benzamide 1a was treated with 2.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Our original plan was to install an acetonitrile group on the aromatic ring through transition‐metal‐catalyzed C(sp 2 )–H activation assisted by 8‐aminoquinoline because the nitrile group plays an important role in bioactive molecules and pharmaceuticals . However, preliminary experimental results showed that a methylation product was actually obtained when 2‐methyl‐ N ‐(quinolin‐8‐yl)benzamide 1a was treated with 2.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Direct cross-dehydrogenative coupling reactions via transformations of C–H bond into other bonds have been established as effective and robust methods for the preparation of valuable fragments of pharmaceuticals and intermediates of natural products . Among them, the oxidative C–H activations of acetonitrile and acetone have been received extensive attention because not only can these groups play an important role in bioactive molecules, pharmaceuticals, and specialty chemicals, but also they can be good approaches toward other valuable synthons . As a consequence, the development of novel and effective strategies to realize C–H activation of acetonitrile and acetone leading to useful structures usually remains to be extremely attractive and significant .…”
Section: Introductionmentioning
confidence: 99%
“…Purines bearing C-substituents at position 2 are available by cyclisation reactions of 4-aminoimidazole-5carboxamides or nitriles with derivatives of carboxylic acids (esters, orthoesters etc.) [6][7][8] , while purines bearing C-substituents at position 8 are prepared by similar cyclisations from 5,6-diaminopyrimidines [9][10] . Other possible approaches to the C-C-purines are radical or nucleophilic substitutions or via generation of carbanions or organometallics (Li, Mg or Zn) on the purine skeleton followed by reaction with electrophiles [11][12][13] .…”
mentioning
confidence: 99%